EVALUATING THE SOFTWARE QUALITY COSTS - N. Lobanova; D. Dubrovin (Вестник университета)
The article gives the arguments proving necessity of evaluating the software quality costs. Questions of evaluating the software quality costs were considered. Various techniques to ensure the software quality were analyzed. A description of the method of Quality Function Deployment was given. The possibility of using the method of Software Quality Function Deployment in the process of software development as a method to reduce the highest costs of quality and improve product competitiveness was considered.